TERAPI CAIRAN PADA ANJING DAN KUCING - Suartha, I Nyoman (Buletin Veteriner Udayana, 2012)
Normally, fluids lost through physiological activities such as respiration, sweating, panting,and urination. Abnormal lost of fluids occurs through vomiting, diarrhea, fever or excessiveurination and disease processes. The purpose of fluid therapy is to replenish the volume ofblood circulations and to replace the normal and excessive fluids lost. Dogs and cats needfluid intake 40 – 60 ml/kg body weight daily to replenish fluids lost through urination andrespiration. In a condition of excessive fluids lost such as diarrhea and vomiting the animalbody needs water replacement as much as 70 – 80% within 24 hours or instantaneouslyreplacement half of the water losses within the first 4 to 8 hours. In conclusions, fluidtherapy is one way for treating emergency condition animals with intensice care. Properlycare should be considered when choosing the right solutions for the fluid therapy
Keywords: small animal, dehydration, crystalloid fluid, intravascular